Alternatywne połączenia logistyczne między Polską i państwami Partnerstwa Wschodniego - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Transport services market is one of the key elements of the economy of each country. Through the transport market the access to factors of production for enterprises is provided and by its mediation products are delivered to consumers. The correctness of functioning of the market determines the efficiency of the whole economic system of the country. For each Eastern Partnership country the EU is the main trade partner. Poland as one of the member states of the European Union is closely cooperating with the Eastern Partnership countries and the key to the development of this cooperation is the insurance of the proper functioning of the transport market. The aim of the article is to present the current logistics connections between Poland and Eastern Partnership countries and problems of logistics connections and as well as alternative connections that create more favorable conditions for the cooperation.
Keywords: Eastern Partnership; transport market; transport infrastructure; logistics